2016
DOI: 10.1111/nep.12634
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum sodium levels with all‐cause and cardiovascular mortality in chronic kidney disease: Results from a prospective observational study

Abstract: Hyponatraemia in the ambulatory setting is associated with all-cause but not cardiovascular mortality in CKD, independent of concomitant medications and co-morbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 28 publications
0
34
0
1
Order By: Relevance
“…These include changes of urine dilution and concentration in response to antidiuretic hormone, and alteration of water and Na and CI reabsorption and excretion 13,14 . Previous studies have reported that dysnatremias and hypochloremia are associated factors for mortality in patients with chronic kidney disease (CKD), with or without dialysis [15][16][17][18][19][20][21][22] . Thus, dyschloremias and dysnatremias have been proposed as potential useful factors for mortality prediction in this population [15][16][17][18][19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…These include changes of urine dilution and concentration in response to antidiuretic hormone, and alteration of water and Na and CI reabsorption and excretion 13,14 . Previous studies have reported that dysnatremias and hypochloremia are associated factors for mortality in patients with chronic kidney disease (CKD), with or without dialysis [15][16][17][18][19][20][21][22] . Thus, dyschloremias and dysnatremias have been proposed as potential useful factors for mortality prediction in this population [15][16][17][18][19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…Several 9 17 but not all 18 , 19 epidemiologic studies reported that hyponatremia is associated with increased all-cause mortality in no-dialysis CKD and maintenance dialysis patients. Similarly, the association of hypernatremia with all-cause mortality risk has also yielded inconsistent results 9 , 11 14 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Another hypothesis is that hyponatremia may be associated with various medical conditions including bone fractures, falls [9,10], cardiovascular events [33], and cognitive dysfunction [3,34], eventually leading to a high mortality rate [29]. Our study showed that the lowest tertile of serum sodium had a higher proportion of comorbidities, although not statistically signi cantly.…”
Section: Discussionmentioning
confidence: 53%